Pengaruh Metode Kooperatif Tipe Round Robin Brainstorming Terhadap Keterampilan Berfikir Siswa Pada Pembelajaran Fiqih MTsS YATI - Dian Afriani; Arifmiboy Arifmiboy; Deswalantri Deswalantri; Januar Januar (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
The background of this research is that the method used by the teacher is not appropriate to the learning needs of students at MTsS Yati Kamang Mudik, the level of critical thinking of students seems less active in expressing opinions, not giving many suggestions or questions, not being able to explain problems, with the influence of the social environment. The purpose of this study was to find out how much influence the use of round robin brainstorming learning methods had on students' critical thinking skills at MTsS Yati Kamang Mudik. This research is a quantitative research. The research design used is quasi-experimental. The sample of this research was class VIII students at MTsS Yati Kamang Mudik with a total sample of 55 students. The research samples were class VIII.1 experiments using the round robin brainstorming method and class VIII.2 controls using the conventional model. The data analysis technique uses the Normality Test with the Kolmogorov Smirnov formula, and the homogeneity test with Fisher's test followed by hypothesis testing with the paired sample test and the Independent test. The results of the study show that based on the results of data processing it can be interpreted that there is a significant influence on the use of the round robin brainstorming method as these results prove that the experimental value of the Sig class. (2-tailed) = 0.00. While the research alpha = 5% or 0.05. That is, the value of Sig. (2-tailed) is smaller than the alpha value (0.00 <0.05) so that there is an influence of the round robin brainstorming method on students' critical thinking skills in Fiqh lessons at MTsS YATI Kamang Mudik class VIII. There are differences in students' critical thinking abilities using the round robin brainstorming method. This can be proven by the average value using the round robin brainstorming method of 75.79. While the control class obtained an average value of 65.59. The use of the round robin brainstorming method is better than the conventional method, in fiqh critical thinking skills using the round robin brainstorming method.